Assembly of an evolutionarily conserved alternative proteasome isoform in human cells - Padmanabhan, Achuth; Vuong, Simone; Hochstrasser, Mark (Cell reports, 2016)
Targeted intracellular protein degradation in eukaryotes is largely mediated by the proteasome. Here, we report the formation of an alternative proteasome isoform in human cells, previously found only in budding yeast, that bears an altered subunit arrangement in the outer ring of the proteasome core particle. These proteasomes result from incorporation of an additional α4 (PSMA7) subunit in the position normally occupied by α3 (PSMA4). Assembly of “α4-α4” proteasomes depends on the relative cellular levels of α4 and α3 and on the proteasome assembly chaperone PAC3. The oncogenic tyrosine kinases ABL and ARG and the tumor suppressor BRCA1 regulate cellular α4 levels and formation of α4-α4 proteasomes. Cells primed to assemble α4-α4 proteasomes exhibit enhanced resistance to toxic metal ions. Taken together, our results establish the existence of an alternative mammalian proteasome isoform and suggest a potential role in enabling cells to adapt to environmental stresses.
Gesehen am 23.10.2020